Přerámcování Řecka v českých mainstreamových psaných médiích - Huleja, Jan (Lidé města, 2013)
We would like to document the radical transformation of the media presentation of Greece and the Greeks that occurred at the time of the so-called crisis on the material of Czech mainstream media texts (linguistic data up to 2009 was gained from the Czech National Corpus, data from the years 2010-2012 is based on the author‘s own excerpts). The media texts dedicated to Greece and the Greeks from the period before the crisis and during the crisis reveal the transformation of the media world, and document the transformation of the frame in which Czechs considered Greece at the end of 2012. This frame of mind is also probably shared with the majority of citizens from the so-called responsible countries of the European Union. Research proves that what was evaluated with positive or neutral attributes before the crisis was later often described with negative attributes. The Greek's "story" has been rewritten - his picture was put into a negative frame. Our paper is based on the theory of frames as presented in the works of E. Goffman, C. J. Fillmore, J. Butler, and especially G. Lakoff, who applies this theory in the field of media communication and indicates its potential as an interpretive tool for grasping the media image of the world.